Personal Branding of Lecturers and Word of Mouth: Effective Education Strategy in Increasing the Attractiveness of Entrepreneurship Study Program and Reputation of Pelita Bangsa University - Harisandi, Prasetyo; Hurriyati, Ratih; Gaffar, Vanessa; Adi Wibowo, Lili; Yanti, Pitri; Yusriani, Sri; Purwanto, Purwanto (IJORER : International Journal of Recent Educational Research, 2025)
Objective: This study is to evaluate the influence of lecturers' personal branding and community conversations on the attractiveness of the Entrepreneurship Study Program and the reputation of Pelita Bangsa University. Method: The sample surveyed was 150 students of the Pelita Bangsa University Entrepreneurship Study Program. With the help of the SmartPLS program, research data were collected from filling out questionnaires and analyzed quantitatively using the SEM PLS analysis technique. Results: This study shows that (1) Personal branding of lecturers has a significant effect on the attractiveness of study programs, (2) positive WOM increases the attractiveness of study programs, (3) Personal branding of lecturers does not have a significant direct effect on university reputation, (4) WOM has a significant effect on university reputation, (5) The attractiveness of study programs functions as a mediator that connects personal branding of lecturers and WOM with university reputation. Novelty: This study creates an integrative model that links lecturer personal branding, word of mouth (WOM), study program attractiveness, and university reputation. Unlike previous studies that addressed each of these factors separately, this study emphasizes that lecturer image and WOM do not directly improve university reputation. In addition, this study incorporates the concept of academic marketing into higher education, which was previously used more in business studies. This opens new eyes.